2015
DOI: 10.1093/icvts/ivv078
|View full text |Cite
|
Sign up to set email alerts
|

Should computed tomography angiography supersede invasive coronary angiography for the evaluation of graft patency following coronary artery bypass graft surgery?: Table 1:

Abstract: Invasive coronary angiography (ICA) has long been the established gold standard in assessing graft patency following coronary artery bypass graft (CABG). Over the past decade or so however, improvements in computed tomography angiography (CTA) technology have allowed its emergence as a useful clinical tool in graft assessment. The recent introduction of 64-slice and now 128-slice scanners into widespread distribution, and the development of 320-detector row technology allowing volumetric imaging of the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…CTA with 128 slices showed low radiation exposure (2.3 ± 0.3 mSv), comparable to ICA [17]. There are limitations to CTA, with difficulties in accurate visualisation of distal anastomoses and clip associated artifacts [18]. The development of technology and integration of CTA with the fractional reserve flow (FFR) improved the visual assessment of graft patency and perfusion with a functional indicator [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…CTA with 128 slices showed low radiation exposure (2.3 ± 0.3 mSv), comparable to ICA [17]. There are limitations to CTA, with difficulties in accurate visualisation of distal anastomoses and clip associated artifacts [18]. The development of technology and integration of CTA with the fractional reserve flow (FFR) improved the visual assessment of graft patency and perfusion with a functional indicator [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between CTA and ICA anatomical assessment was moderate for multivessel evaluation ( 11 ). Moreover, the inaccurate visualization of distal anastomoses and clip artifacts might affect the diagnostic accuracy of CTA ( 21 ). Study had indicated that patients with prior CABG who received percutaneous coronary intervention (PCI) had better in-hospital clinical outcomes compared with those who received medical management alone ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are emerging data on the value of coronary graft imaging with computed tomography (CT) in this setting . It has been shown that 64‐slice CT angiography is a reliable method for the assessment of bypass grafts in an unselected “real‐world” patient population, with very high sensitivity and specificity for the detection of bypass graft stenosis or occlusion (97%) .…”
Section: Discussionmentioning
confidence: 99%